Silas W. Porter, The Municipal Code of Monmouth 168-69 (1883) - (:unkn) unknown (My University, 1883)
Art. 6, §§ 654-662: It shall be unlawful for any person, within the corporate limits of the city, to carry or wear under his clothes, or concealed about his person, any pistol, colt or slung shot, cross knuckles, or knuckles of lead, brass or other metal, or bowie knife, dirk knife, or dirk, razor or dagger, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED